A Comparison of Continuum and Cell-based Models of Colorectal Cancer - Walter, Alexander (2009)
Colorectal cancer is thought to originate in the epithelial cells that line the colorectal crypt and, in most cases, is associated with a mutation in Wnt-signalling pathway. These mutations cause cells to alter their proliferative behaviour, make their cytoskeleton less deformable and increase their levels of cell-cell and cell-substrate adhesion.